Accountability perception of Thai Government: to whom and what counts. Issue 1 (4th March 2019) - Komutputipong, Natchanont; Keerasuntonpong, Prae
Abstract : Purpose: Public sector entities face conflicting demands from stakeholders. The literature suggests identifying and prioritizing stakeholders can improve accountability. Thailand, an emerging economy, and currently under military rule, provides an interesting context to investigate stakeholder tensions. The purpose of this paper is to investigate how and why the Thai Government bureaucrats prioritize their stakeholders. Design/methodology/approach: The study draws on the managerial branch of stakeholder theory and stakeholder salience theory to examine the importance of various stakeholders and of the stakeholders' salient attributes perceived by the Thai Government bureaucrats in discharging its accountability. The study uses a survey questionnaire mailed out to the central government departments in Thailand. Findings: The study finds that single most important stakeholder is the Office of the Auditor-General. The public is perceived as the second. This is dissimilar to the western-centric accountability focus on the public, and challenges claims by the Thai military coup that it will bring democratic rule. "Legal power" supporting the stakeholders' claims for government accountability is the most influential attribute in determining stakeholder importance and prioritizing attention for government bureaucrat's discharge of its accountability. Originality/value: Such findings increase understanding of the applicability of stakeholder theory and stakeholder salience theory in the context of military rule in emerging economy countries such as Thailand. This paper also provides suggestions of how stakeholders may shape their salience in order to gain priority. This also provides an immediate suggestion for reforms of the Thai regulatory frameworks in prioritizing stakeholders and promoting the government's greater accountability.